(untitled) (International Journal of Nursing Education, 2019)
Obesity considered as a medical problem in many under developing and developed countries across the world. Many researchers are working towards reduction of obesity because it leads to many life threatening diseases like coronary heart diseases hypertension, non-insulin dependent diabetes, pulmonary dysfunctions, osteoarthritis and certain types of cancers. Obesity is a growing health issue worldwide specifically in India there is growing prevalence of obesity and India is the third most obese country in the world, just behind US and China. In such scenario the rise in obesity and obesity related disorders focuses on the increasing effect of lifestyle changes specifically eating habits i.e. misconception of junk food. The solution to this problem is to have healthy lifestyle speaking of which opens a lot of doors from exercise to food. Reduction of the weight among obese is beneficial which helps to reduce the risk for mortality and morbidity. All the health care professionals especially in the field of Community Health Nursing must take an extensive effort to educate the people to follow healthy life style practices in reduction of weight and make efforts to reduce the obesity. Hence the researcher felt need of conducting the research on reduction of weight among obese young adult girls as it is a major modifiable risk factors disease in the world. The aim of the study was to assess the effectiveness of green tea in reduction of body weight among obese young adult girls. Objectives: 1. To assess the obesity among young adult girls by using BMI calculation. 2. To assess the effectiveness of Green tea on weight reduction among obese young adult girls. 3. To find out the association between the post test weight of obese young adult girls with their selected demographic variables.